"Improve Their Condition While Making Them Useful": Colonia General Conesa and the Dynamics of Settler Colonialism in Nineteenth-Century Argentina. - Greenwald, Hannah (Hispanic American Historical Review, 2023)
In 1879, as the Argentine army prepared a military campaign against Indigenous groups in the Pampas and Patagonia, the national government created an Indigenous colony called Colonia General Conesa. Conesa's inhabitants were expected to build homes and cultivate crops under military watch and become "useful" Argentine citizens in the process. This short-lived assimilationist project, which the government abandoned three years later, illuminates the rapidly shifting dynamics of Argentine settler colonial ideology. Although Argentine officials initially saw Conesa as an expedient resolution to the nation's so-called "Indian question," the dissolution of the southern frontier line in the early 1880s necessitated a shift toward new strategies that emphasized the complete physical and discursive erasure of the region's Indigenous peoples. Conesa's history, situated within the broader context of interethnic relations in Argentina's southern borderlands, sheds light on the development of Argentine settler colonialism and exemplifies how Indigenous people were written out of the nation's history.